Nanotechnology and the Challenges of Equity, Equality and Development - Cozzens, Susan E.; Wetmore, Jameson; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Nanotechnology is enabling applications in materials, microelectronics, health, and agriculture, which are projected to create the next big shift in production, comparable to the industrial revolution. Such major shifts always co-evolve with social relationships. This book focuses on how nanotechnologies might affect equity/equality in global society. Nanotechnologies are likely to open gaps by gender, ethnicity, race, and ability status, as well as between developed and developing countries, unless steps are taken now to create a different outcome. Organizations need to change their practices, and cultural ideas must be broadened if currently disadvantaged groups are to have a more equal position in nano-society rather than a more disadvantaged one. Economic structures are likely to shift in the nano-revolution, requiring policymakers and participatory processes to invent new institutions for social welfare, better suited to the new economic order than those of the past.
Keywords: Social sciences; Ethics; Medical research; Quality of life; Nanotechnology; Social Sciences; Social Sciences, general; Nanotechnology; Ethics; Quality of Life Research; Electronic books